Autumn : an alphabet acrostic - Schnur, Steven; Evans, Leslie (New York : Clarion Books, 1997)
Describes the autumn season, with its animals, rain, cold winds, and harvested food. When read vertically, the first letters of the lines of text spell related words arranged alphabetically, from "acorn" to "zero.".
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
3.2
K-3
Keywords: Autumn -- Juvenile literature; Acrostics -- Juvenile literature; Autumn; Acrostics; Alphabet; Autumn; Literary recreations; Puzzles; Alphabet; Autumn; Acrostics; Alphabet